2013
DOI: 10.1073/pnas.1308306110
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectron tomography reveals the sequential assembly of bacterial flagella in Borrelia burgdorferi

Abstract: Periplasmic flagella are essential for the distinctive morphology, motility, and infectious life cycle of the Lyme disease spirochete Borrelia burgdorferi. In this study, we genetically trapped intermediates in flagellar assembly and determined the 3D structures of the intermediates to 4-nm resolution by cryoelectron tomography. We provide structural evidence that secretion of rod substrates triggers remodeling of the central channel in the flagellar secretion apparatus from a closed to an open conformation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
154
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(169 citation statements)
references
References 50 publications
8
154
0
Order By: Relevance
“…The secretion channel appeared to be closed at the base, presumably to prevent leakage ( Fig. 2 C and H), reminiscent of findings for the flagellar motor of Borrelia burgdorferi (28).…”
Section: The Presence Of Mxin or Spa33 Has A Dramatic Impact On T3ss supporting
confidence: 68%
See 1 more Smart Citation
“…The secretion channel appeared to be closed at the base, presumably to prevent leakage ( Fig. 2 C and H), reminiscent of findings for the flagellar motor of Borrelia burgdorferi (28).…”
Section: The Presence Of Mxin or Spa33 Has A Dramatic Impact On T3ss supporting
confidence: 68%
“…Two different procedures were used to collect and analyze the tomographic data. Initially, low-dose tilt series were collected at 15,500× magnification and 2 × 2 binning, similar to our previous procedure (28). Subsequently, we collected tilt series in dose fractionation mode, which enabled us to correct the motion-induced image blurring (29) and effectively improve the quality of the final reconstructions.…”
Section: Cryoelectron Tomography Of Shigella Minicells Reveals Intactmentioning
confidence: 99%
“…It has been suggested that the assembly of the rod is a cooperative process (15). Furthermore, a recent study showed, by cryo-electron microscopy, that the rod structure undergoes rearrangement and acquires the typical rod shape only after the addition of FlgF (38). It is known that the rod components belong to the same export specificity class (23).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequence analysis of B. burgdorferi MotA and MotB indicates that they share 24% and 45% identity, respectively, with those in E. coli (21). Genome sequence analyses as well as cryoelectron tomography (cryo-ET) data suggest that spirochetal periplasmic flagella are similar to E. coli flagella in many aspects (22)(23)(24), although the regulation of motility and chemotaxis genes are distinctive (11,25). While B. burgdorferi motility and chemotaxis genes identified to date are transcribed by the housekeeping 70 factor of RNA polymerase, those genes in E. coli are regulated in a hierarchical manner (11,25,26).…”
mentioning
confidence: 99%
“…While B. burgdorferi motility and chemotaxis genes identified to date are transcribed by the housekeeping 70 factor of RNA polymerase, those genes in E. coli are regulated in a hierarchical manner (11,25,26). A periplasmic flagellum is composed of at least 50 proteins that can be subdivided into three major parts: the basal body-motor-switch complex, the hook, and the filament (24,27).…”
mentioning
confidence: 99%